Albumin-corrected anion gap predicts acute kidney injury in critically ill patients with acute pancreatitis: a retrospective cohort study - Zheng Wang; Haoyu Zhang; Xiaozhou Xie; Feng Cao; Fei Li (BMC Nephrology)
Abstract Background Acute kidney injury (AKI) is a common and serious complication of acute pancreatitis. Early detection of patients at high risk for AKI is critical to avoiding complications and lowering mortality. This study looked into the relationship between albumin-corrected anion gap (ACAG) and AKI in critically ill patients with AP. Methods All eligible patients from the Medical Information Marketplace for Critical Care IV database were considered for this study. Kaplan-Meier curves estimated the cumulative risk of AKI and in-hospital mortality. Restricted cubic splines (RCS) and multivariate Cox regression models explored the relationship between ACAG and AKI. Subgroup analyses evaluated the result robustness. Results A total of 714 patients were included (mean ACAG: 20.15 ± 5.64; in-hospital mortality: 13.87%; AKI incidence: 70.87%). Kaplan–Meier analysis revealed that the ACAG ≥ 20.25 group exhibited significantly higher AKI incidence and renal replacement therapy(RRT) requirement risk (P < 0.001). Multivariable Cox regression demonstrated ACAG independently associated with AKI risk in AP patients—both as a continuous (HR: 1.12 [95% CI: 1.04–1.21], P = 0.004) and categorical variable (HR: 1.89 [95% CI: 1.11–3.23], P = 0.020). Restricted cubic spline modeling confirmed a linear association between ACAG and increasing AKI risk. Conclusion Elevated ACAG levels (≥ 20.25 mmol/L) at ICU admission is associated with a high risk of AKI in critically ill patients with AP.